2022
DOI: 10.5539/jel.v11n5p44
|View full text |Cite
|
Sign up to set email alerts
|

What Apps Do Postsecondary Students with Attention Deficit Hyperactivity Disorder Actually Find Helpful for Doing Schoolwork? An Empirical Study

Abstract: Attention Deficit Hyperactivity Disorder (ADHD) experts and individuals with ADHD have made many recommendations concerning mobile apps that could potentially help college students succeed. But do students know about these recommended apps? Do they find them useful? How do students use mobile apps for completing schoolwork? To answer these questions we carried out two empirical studies. In study 1, 35 Canadian postsecondary students who self-reported ADHD and 74 students without disabilities completed an onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Mandatory attendance during live lectures was perceived as a requirement for a beneficial effect of recorded lectures. While, previous literature supports the finding that recordings are beneficial, the recommendation for mandatory attendance has not been found (Fichten et al, 2021). Also, regarding lectures, mandatory post-test could be beneficial for students with ADHD since it increases engagement.…”
Section: Practical Implicationsmentioning
confidence: 90%
“…Mandatory attendance during live lectures was perceived as a requirement for a beneficial effect of recorded lectures. While, previous literature supports the finding that recordings are beneficial, the recommendation for mandatory attendance has not been found (Fichten et al, 2021). Also, regarding lectures, mandatory post-test could be beneficial for students with ADHD since it increases engagement.…”
Section: Practical Implicationsmentioning
confidence: 90%
“…When 25 minutes have elapsed, or if the user elects to end the session early, the video and audio recorded from the webcam are stored in AWS S3 cloud storage. The 25-minute duration was chosen because prior research has shown that students with ADHD commonly use the Pomodoro technique [10], which involves working in 25-minute sessions followed by 5-minute breaks to ensure that focus-intensive tasks are interspersed with short breaks [13,18]. This method is consistent with the "time on-time off" approach to allocating schoolwork time that many practitioners recommend for students with ADHD [23].…”
Section: Interaction Designmentioning
confidence: 99%
“…We also checked the past three years of ADDitude Magazine, as well as web sites and Facebook groups. In Table 2, (Fichten et al, 2022) we present an annotated listing of the 20 schoolwork related apps mentioned by at least two sources and available in the Apple App Store and/or the Google Play Store. We were unable to find any studies that actually showed whether students knew about these apps and whether they liked them for doing academic work.…”
Section: Apps and Mobile Devicesmentioning
confidence: 99%
“…We were unable to find any studies that actually showed whether students knew about these apps and whether they liked them for doing academic work. Therefore, in 2020 we used an online LimeSurvey to ask 35 students with ADHD and 74 students without disabilities whether they used any of the 20 recommended apps, and if yes, which ones they found helpful (Fichten et al, 2022). Both groups of students were familiar with: Asana, Dragon, Dropbox, Due, Evernote, Forest, Google Calendar, IFTT, Pomodoro Timer, Quizlet, Read&Write, and Microsoft To Do / Wunderlist.…”
Section: Apps and Mobile Devicesmentioning
confidence: 99%